GC-MS METABOLITE PROFILING, TOTAL PHENOLIC, ANTIOXIDANT ACTIVITY, AND IN SILICO APPROACH IN CHRONIC ANTI-INFLAMMATORY ETHANOL EXTRACTS OF POLYSCIAS SCUTELLARIA (BURM. F.) FOSBERG LEAVES - SYARIFUDDIN, ALFIAN; NURROCHMAD, ARIEF; FAKHRUDIN, NANANG (International Journal of Applied Pharmaceutics, 2025)
Objective: Polyscias scutellaria has been recognised as a medicinal herb with therapeutic potential. Various studies have identified bioactive compounds in this plant that exhibit a range of biological activities, including anti-proliferative, anti-inflammatory, anti-parasitic, and anti-diabetic properties. Methods: This study aimed to profile the Extract Ethanol Polyscias scutellaria (EEPS) metabolites using gass chromatography mass spectrometry (GC-MS) and predict their activities against four anti-inflammatory receptors obtained from the Protein Data Bank (RCSB PDB), cycloxygenase-2 (COX-2) (5IKT), interleukin-6 (IL-6) (1ALU), Interleukin-1 beta (IL-1β) IL-1 β (8C3U), and tumor necrosis factor alpha (TNF-α), TNF-α (7JRA) using AutoDock 1.5.6 software. Validation of the native ligands were carried out using the root mean square deviation (RMSD) value, and the total phenolic compounds were also examined using Spectrophotometry Ultra Violet-Visible (UV-Vis). Furthermore, the UV-Vis was also used to test the 2,2-azinobis-3-Ethylbenzothiazoline-6-Sulfonic Acid (ABTS) and Ferric Reducing Antioxidant Power (FRAP). Results: The Total Phenol Content (TPC) is 131.458±8.818 ppm, and during the FRAP assay, EEPS showed the highest IC50 value, measured at 54.66±2.35 μg/ml, which was significantly higher than that of ascorbic acid (10.10±0.14 μg/ml). Similarly, in the ABTS assay, EEPS exhibited an IC50 of 55.13±1.19 μg/ml, exceeding the IC50 of ascorbic acid (10.47±0.29 μg/ml). Although GC-MS analysis identified eight compounds, molecular docking was performed only on the two most abundant and structurally similar compounds: (S, Z)-Heptadeca-1,9-dien-4,6-diyn-3-ol and phytol. Native ligands were validated with RMSD values of less than 2 Å. Conclusion: Molecular docking showed that (S-Z)-Heptadeca-1,9-dien-4,6-diyn-3-ol binds better to the COX-2 and IL-6 receptors than Phytol. However, phytol binds better to the TNF-α and IL-1β receptors. These findings suggest potential anti-inflammatory activity, but further in vitro and in vivo studies are necessary to confirm their biological effects.